Structural similarity index (SSIM) revisited: A data-driven approach - Bakurov, Illya (2022)
Bakurov, I., Buzzelli, M., Schettini, R., Castelli, M., & Vanneschi, L. (2022). Structural similarity index (SSIM) revisited: A data-driven approach. Expert Systems with Applications, 189, 1-19. [116087]. [Advanced online publication on 27 October 2021]. https://doi.org/10.1016/j.eswa.2021.116087-----------------------------------------Funding Information: This work was supported by national funds through the FCT (Funda??o para a Ci?ncia e a Tecnologia), Portugal by the projects GADgET (DSAIPA/DS/0022/2018), BINDER (PTDC/CCIINF/29168/2017), and AICE (DSAIPA/DS/0113/2019). Mauro Castelli acknowledges the financial support from the Slovenian Research Agency, Slovenia (research core funding no. P5-0410).